Selection of grain sorghum varieties for the north Caucasian region of Russia - N. A. Kovtunova; V. V. Kovtunov; A. E. Romanyukin; V. A. Shurshalin; G. M. Ermolina (Зерновое хозяйство России, 2023)
It is possible to solve the problem of productivity and improve the gross harvest of agricultural products by introducing new varieties and hybrids adapted to the conditions of cultivation into production. The diversity of the varietal composition of sorghum crops necessitates a careful approach in the selection of varieties. This is especially important for the North Caucasus region, which is characterized by contrasting natural and climatic conditions. The purpose of the current study was to analyze the existing varietal range of grain, sweet, grass sorghum, to identify varieties recommended for cultivation in the North Caucasus region. The work on the development of sorghum crops was carried out at the Federal State Budgetary Scientific Institution “ARC “Donskoy” in accordance with the Methodology of the State Commission for Variety Testing of Agricultural Crops. There has been found that since 2013 20 grain sorghum varieties and hybrids of Russian originators (7 sugar sorghum varieties, 6 Sudan grass varieties, 7 sorghum-Sudan hybrids) have been approved for cultivation in the North Caucasus region of the Russian Federation. Since 2013 2 grain sorghum varieties, 2 sweet and Sudan grass varieties, 1 sorghum-Sudan hybrid have been developed and introduced into the Register at ARC “Donskoy”. There have been developed grain sorghum varieties ‘Zernogradskoye 88’, ‘Esaul’ which are distinguished by high grain productivity of 5.0–6.2 t/ha and have been recommended for use for feed and food purposes. Sweet sorghum varieties ‘Feniks’ and ‘Yuzhnoe’ have been characterized by a large productivity of green mass for silage (37–45 t/ha) and good feed qualities, which allows them to be used for silage production. Sudan grass varieties ‘Alisa’ and ‘Gratsiya’ have made it possible to obtain 2 cuttings of high-quality green fodder (39–44 t/ha) and hay (12.0–13.2 t/ha). The sorghum-Sudan hybrid ‘Dobrynya F1’ has 55–61 t/ha of green mass for two cuttings and could be recommended for use for green fodder, hay, silage.